lucanid Beetle Species and Subspecies (Coleoptera, Lucanidae) recorded in Vietnam - Dap, Dang Thi; Du, Tran Thieu (Academia Journal of Biology, 2015)
A total of 134 species and subspecies of 21 genera belonging to the lucanid family (Coleoptera, Lucanidae) in Vietnam were listed. Among them, 2 species were firstly recorded for the entomofauna of Vietnam from specimens of IEBR Zoological Museum: Dorcus arrowi Boileau, 1911 and Lucanus kraatzi Nagel, 1926. Most of stage beetles were collected in high forest mountains such as Tamdao (Vinhphuc province), Sapa (Laocai province), Dalat (Lamdong province). Many lucanid beetles species have been hunt down for the commerce with foreign countries.